IMPLEMENTATION OF THE COVID-19 RISK COMMUNICATION POLICY IN PANDEGLANG 2022 - Salimah, Nahda; Sulistiadi, Wahyu (Journal of Indonesian Health Policy and Administration, 2022)
Currently, the world is experiencing a non-natural disaster, the COVID-19 pandemic. The Indonesian Government issued instructions for handling and controlling COVID-19 by implementing health protocols and vaccinations to reduce the rate of COVID-19 cases. The handling and control of COVID-19 are delivered by increasing public knowledge about COVID-19 through a risk communication approach. Pandeglang area, Banten, had the lowest dose one and two vaccination coverage rates in Banten Province in 2021. Implementing the risk communication policy needs to be considered in successfully handling and controlling COVID-19. This research is qualitative with case study type research. The method of collecting data is using in-depth interviews. In-depth interviews were conducted with four informants. The informants came from Pusdalops – PB BPBD Pandeglang Region, Health Promotion Division and Disease Prevention and Control Division, Pandeglang District Health Office. This study aims to analyze the implementation of risk communication policies carried out by BPBD and the Health Office in handling and controlling COVID-19 in the Pandeglang Region. The analysis results show that the risk communication policies' standards and targets are divided into clear communication action plans between BPBD and the Health Office. However, there was an obstacle in the availability of the program's budget. The budget was diverted for handling and controlling COVID-19 situations. In addition, the working period of the head of the organization is felt to be a barrier to inter-organizational relations because it takes time to adapt to re-coordinate with the new leader.